Analisis Gestur Tubuh Mahasiswa Universitas Islam Negeri Sumatera Utara dalam Kelas Virtual Perspektif Teori Komunikasi Nonverbal - Ade Nurlita; Irma Yusriani Simamora (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2026)
This study examines the body gestures of students at Universitas Islam Negeri Sumatera Utara in virtual classrooms, lecturers’ responses to these gestures, and the meanings implied in students’ nonverbal behavior from a theoretical perspective. The research addresses how nonverbal communication shapes engagement in post-pandemic online learning environments. Using a qualitative descriptive approach, data were collected through observation of student interactions via the Zoom platform and analyzed using George Kelly’s gesture theory and Vijai Kumar’s gesture theory. The findings indicate that students’ gestures are predominantly adaptive (adaptors) rather than illustrative or regulatory, reflecting intrapersonal psychological states such as confusion, boredom, hesitation, or cognitive processing. These gestures often create ambiguity due to limited verbal clarification. The study argues that Kumar’s framework is more applicable for assessing real-time student engagement, while Kelly’s theory provides deeper insight into students’ cognitive construction of learning experiences. The results highlight that weak nonverbal interaction contributes to reduced effectiveness of online learning, suggesting the need for lecturers to incorporate awareness of gesture theory and nonverbal communication strategies to foster meaningful virtual classroom engagement.